Принципы построения системы для измерения магнитного момента технического объекта на основе сигнатур вращения - Гетьман, А.В.; Крамчанин, Е.Г. (Технічна електродинаміка, 2012)
Theoretical aspects of the practical definition of the magnetic moment with the help of mathematical processing of the signatures of rotation of a technical object were considered. Theoretically justified procedure for determining the magnetic moment on the basis of the integrated processing of magnetic flux produced by rotation of a technical object inside the contour measuring syste. The principles of management of the contour system for measuring the magnetic moment in the angular displacement of technical facility were considered. Propose a functional diagram of the control system and the features of its implementation.